TRANSLATION METHODS USED IN WRITING INDONESIAN SUBTITLES OF “KUNG FU PANDA HOLIDAY” - NURMALLAH, HERDIANTI (Jurnal Ilmiah Mahasiswa FIB, 2013)
In Indonesia, western movies that are spoken in English make the need for Indonesian subtitles increase. To make subtitles in different language, translation has an important role. The translator must use appropriate methods to produce good translation. This study aims to find out the kinds of translation methods used in writing Indonesian subtitles of the movie “Kung Fu Panda Holiday” by using Newmark’s theory (1988). This study uses descriptive qualitative approach with document analysis. The data are the English and Indonesian subtitles of “Kung Fu Panda Holiday” containing complex sentences and compound sentences. The result shows that four utterances are translated using faithful translation, eight utterances are translated using semantic translation, one utterance is translated using free translation, two utterances are translated using idiomatic translation, and twenty utterances are translated using communicative translation. The translation methods mostly used by the translator is communicative translation. The result of communicative translation is very understandable for the TL reader especially for the audiences of an animation movie watched by people of all ages.         Kata Kunci : penerjemahan, metode penerjemahan, anak judul intrabahasa, “Kung Fu Panda Holiday”